An Evaluation of Oxidative Status in Serum and Breast Milk of Mothers Giving Birth Prematurely and at Full-Term - Abuhandan, Mahmut (Iran J Pediatr, 2015)
BACKGROUND: Burning fat and carbohydrates to provide energy in biological systems causes the formation of free oxygen species. OBJECTIVES: This study aimed to evaluate the oxidative status of serum and breast milk of mothers giving birth prematurely and at full-term. MATERIALS AND METHODS: The study comprised 50 mothers who gave birth at full-term at more than 38 weeks and 43 mothers who gave birth pre-term at below 32 weeks. On the postnatal 5th day, samples of the mother’s milk and serum were taken and stored at -80°C until the study day. On the study day, the total oxidant and total antioxidant levels were measured using the Erel method and the oxidative stress index (OSI) was calculated. RESULTS: While the total oxidant level and total antioxidant level values of the milk of the premature birth mothers were found to be significantly high compared to those of the full-term birth mothers (P = 0.001), no statistically significant difference was found in the oxidative stress index values (P > 0.05). No statistically significant difference was found in the total oxidant level and oxidative stress index values of the serum of the premature birth mothers compared to those of the full-term birth mothers, while the total antioxidant level was found to be significantly low (P = 0.04). CONCLUSIONS: The oxidants and antioxidants in the milk of mothers giving birth prematurely were found to be significantly higher than those of full-term birth mothers. This can be evaluated as the milk of the premature birth mothers providing increased antioxidant defense to protect the infant.